2004
DOI: 10.1001/archotol.130.5.541
|View full text |Cite
|
Sign up to set email alerts
|

GJB2 Gene Mutations in Cochlear Implant Recipients

Abstract: Objective: To determine the prevalence of GJB2 gene mutations in patients undergoing cochlear implantation (CI) and their impact on rehabilitative outcome following implantation. Design: Prospective determination of GJB2 mutation by sequence analysis by denaturing high-performance liquid chromatography and its correlation with outcome following CI. Settings: Two tertiary academic medical centers. Patients: Subjects who have met the audiologic criteria and have undergone CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…These factors can affect our understanding of the presumed phenotype of children with GJB2 mutations. Some studies have shown better outcomes in children with GJB2-related deafness in regards to auditory perception and speech intelligibility [11,12,22], while others have shown no difference in outcomes based on the etiology of deafness [9,10,13,23]. If the majority of children identified with GJB2-related deafness did not have other risk factors affecting developmental outcomes, the effectiveness of a cochlear implant may indeed be encouraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors can affect our understanding of the presumed phenotype of children with GJB2 mutations. Some studies have shown better outcomes in children with GJB2-related deafness in regards to auditory perception and speech intelligibility [11,12,22], while others have shown no difference in outcomes based on the etiology of deafness [9,10,13,23]. If the majority of children identified with GJB2-related deafness did not have other risk factors affecting developmental outcomes, the effectiveness of a cochlear implant may indeed be encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study on the impact of cochlear implants on rehabilitative outcomes and GJB2-related deafness, Lustig et al described two children (out of eight total) with a single heterozygous deafness allele. One child had a physical disability and both had non-syndromic mental disabilities which made testing of these subjects difficult [9]. Although not all outcome studies have found the occurrence of additional disabilities among cochlear implant recipients with GJB2-related deafness [10][11][12], some reports have excluded children with additional disabilities [8,13], making it difficult to understand the potential for co-occurrence of these disabilities in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have compared speech perception in CI children relative to the presence/absence of GJB2 mutations. While some authors point to better results in the GJB2 group [13], others find no significant differences between both groups, with and without mutations in GJB2 [14].…”
Section: Introductionmentioning
confidence: 91%
“…Through careful selection of a population they were able to demonstrate that the GJB2-positive group achieved a higher reading score, thus implicating an absence of central processing disorders. Four publications did not find any better results for patients harbouring GJB2-mutations [16][17][18][19]. However, in the study by Lustig et al only 3 individuals with hearing loss due to GJB2-Mutation were included, a sample size much too small for reliable statistical analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Concerning the latter, a number of studies have examined GJB2-related deafness, because improved counselling for this large group of CI-recipients would be beneficial. 5 of them showed better performance in GJB2-patients [11][12][13][14][15], and 4 found no difference in performance between the two groups [16][17][18][19]. The controversial statements of these studies, partially due to small sample size, lack of proper statistical analysis or short follow-up, prompted us to determine in a retrospective study whether in the Swiss Objectives: A controversy exists in the literature regarding better auditory performance of cochlear implanted children with mutations in the Gap-Junction-Protein Beta2 (GJB2) gene.…”
Section: Introductionmentioning
confidence: 94%